HUBUNGAN DESINFEKSI SINAR ULTRAVIOLET (UV) DENGAN KUALITAS BAKTERIOLOGIS AIR MINUM PADA DEPOT AIR MINUM ISI ULANG (DAMIU) (Studi di Kecamatan Pontianak Selatan Kota Pontianak) - Sustika Navratinova; Nurjazuli Nurjazuli; Tri Tarwatjo (Jurnal Kesehatan Masyarakat (Undip), 2019)
The increase in the number of depots must be accompanied by monitoring the quality of safe drinking water for the public as consumers. There are several causes of drinking water in the depot contaminated with coliform bacteria, one of which is the lack of UV light disinfection in the drinking water treatment process. This disinfection process is very important in the process of drinking water in killing coliform bacteria. The purpose of this study was to determine the relationship of UV light disinfection process with bacteriological quality in DAMIU in the South Pontianak Subdistrict, Pontianak City. This study is an analytic observational study with a cross sectional study design approach. The sample from this study was 30 DAMIU in South Pontianak Sub-district which was taken based on purposive sampling. Data analysis using Chi Square Test. The measurement results are 4 DAMIU which have a less good lamp usage period, 16 DAMIU with a long time to fill the water into a bad gallon, 30 DAMIU has a lamp size that meets the requirements. 6 DAMIU does not meet the bacteriological quality requirements for raw water. 7 DAMIU does not fulfill hygiene sanitation requirements and bacteriological quality of drinking water. The results of the relationship indicate that there is a relationship between hygiene sanitation (p = 0,000) with bacteriological quality of drinking water. However, there was no significant relationship between the use of UV lamps (p = 1,000), the duration of filling water into gallons (p = 1,000), and the bacteriological quality of raw water (p = 0.120) with bacteriological quality of drinking water. The conclusion of this study is that there is no correlation between UV light disinfection process and bacteriological quality of drinking water. It is recommended to the related agencies to keep conducting guidance and checking the quality of DAMIU water regularly.…………………………………….